Jesuits' medical and pharmaceutical manuscripts and the diets recommended for the sick (Brazil and Goa, 18th century) - Viotti, Ana Carolina de Carvalho [UNESP] (Univ Estadual Londrina, 2021)
The corporal treatment of the people occupied a central place in the Jesuits' missionary activity. In addition to attending to patients in hospitals and infirmaries, religious from the Society of Jesus produced and recorded their medical and pharmacological knowledge in documents that, roughly speaking, can be called notebooks or collections of recipes. Amidst the manuscript documents of such typology that can be found in the Portuguese possessions in America and Asia, three of them, produced in the Eighteenth century, will be analysed: an anonymous one - which describes the Jesuit's apothecaries from the four corners of the world, another on from Goa, India and, finally, one attributed to the Jesuits, found in Brazil. The dietary recommendations that accompanied these drug formulas will be scrutinized, seeking to underline what should be consumed, avoided, or prohibited for patients during treatments. By considering these indications, the main objective of this brief essay is to perceive their understanding about illness and cure - including the most frequent ailments, as they deserved attention, and the references that supported their prescriptions -, in addition to the elements available to heal the sick.
Keywords: Jesuit; Medicine; Pharmacy; Diet; Eighteenth century